2013
DOI: 10.2478/s11687-013-0136-0
|View full text |Cite
|
Sign up to set email alerts
|

Baylisascaris sp. infection in a pet kinkajou Potos flavus

Abstract: The nematodes of genus Baylisascaris are common intestinal roundworms of carnivores such as raccoons, skunks, badgers, martens and bears. This report describes Baylisascaris sp. infection in a pet kinkajou Potos flavus imported into Japan from Guyana. Nematode eggs were detected in feces of the juvenile kinkajou in 2011 during a routine veterinary examination. A sequence analysis of the ITS2 nuclear target clustered the examined isolate with B. procyonis and B. columnaris, with 7.8 — 8.8 % base differences fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…These phylogenetic analyses represent preliminary assessments of species relationships within Baylisascaris . Monophyly of the genus was supported for most inference methods and genes (Taira et al, 2013; Xie et al, 2013; Tokiwa et al, 2014), and two well-supported clades have consistently been resolved: clade 1 consisting of B. procyonis , B. columnaris ; and clade 2 consisting of B. ailuri , B. schroederi , B. transfuga . A recent analysis placed B. potosis as monophyletic with B. procyonis and B. columnaris (Tokiwa et al, 2014) based on 28S rDNA and cox1 .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…These phylogenetic analyses represent preliminary assessments of species relationships within Baylisascaris . Monophyly of the genus was supported for most inference methods and genes (Taira et al, 2013; Xie et al, 2013; Tokiwa et al, 2014), and two well-supported clades have consistently been resolved: clade 1 consisting of B. procyonis , B. columnaris ; and clade 2 consisting of B. ailuri , B. schroederi , B. transfuga . A recent analysis placed B. potosis as monophyletic with B. procyonis and B. columnaris (Tokiwa et al, 2014) based on 28S rDNA and cox1 .…”
Section: Introductionmentioning
confidence: 87%
“…Genetic analyses of Baylisascaris species have been limited, but sequence data from certain species has been used to investigate: 1) phylogenetic relationships among species in order Ascaridida (Nadler, 1992; Nadler and Hudspeth, 1998, 2000; Xie et al, 2011a, 2011b, 2013; Li et al, 2012; Liu et al, 2014); 2) detection of species from fecal samples ( B. procyonis , Dangoudoubiyam et al, 2009, Gatcombe et al, 2010; B. transfuga , De Ambrogi et al, 2011; B. schroederi , Zhou et al, 2013); 3) identification of adults from different hosts ( B. devosi , Tranbenkova and Spiridonov, 2017; B. schroederi , Lin et al, 2012; Zhao et al, 2012; B. transfuga , Testini et al, 2011) or geographic areas (Davidson et al, 2013); 4) species delimitation of B. procyonis and B. columnaris (Franssen et al, 2013; Choi et al, 2017); and 5) descriptions of new species ( B. ailuri , He et al, 2008, cited in Xie et al, 2011a; B. potosis , Taira et al, 2013 and Tokiwa et al, 2014; B. venezuelensis , Pérez Mata et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The roundworm of kinkajous was previously thought to be B. procyonis (Kazacos et al 2011;Overstreet 1970). Genetic and morphological analysis revealed that the roundworm of kinkajous differed from B. procyonis (Taira et al 2013), and has been newly described as B. potosis (Tokiwa et al 2014). Kinkajous (Potos fl avus) belong to the family Procyonidae and are closely related to the raccoon (Procyon lotor), which is the natural fi nal host of B. procyonis.…”
Section: Introductionmentioning
confidence: 99%
“…2011 ; Overstreet 1970 ). Genetic and morphological analysis revealed that the roundworm of kinkajous differed from B. procyonis ( Taira et al . 2013 ), and has been newly described as B. potosis ( Tokiwa et al .…”
Section: Introductionmentioning
confidence: 99%
“…Ocular and cerebral baylisascariasis has been reported about 50 times in people, and the number of reported cases annually appears to be increasing (Kazacos, ; Sircar et al., ). This is likely due to better diagnostics and awareness of the disease, although factors such as increasing raccoon densities, geographic expansion of the parasite and involvement of alternate definitive hosts (dogs, some exotic pets) may be involved (Blizzard, Yabsley, Beck, & Harsch, ; Lee, Schantz, Kazacos, Montgomery, & Bowman, ; Page, Gehrt, Cascione, & Kellner, ; Taira, Une, Šnábel, & Sugiyama, ; Yabsley and Sapp, ). While clinical reports in humans are rare, the consequences are severe as the case fatality rate is >40%, and full recoveries are uncommon (Kazacos, ).…”
Section: Introductionmentioning
confidence: 99%